2017
DOI: 10.4274/tjh.2016.0450
|View full text |Cite
|
Sign up to set email alerts
|

Current Review of Iron Overload and Related Complications in Hematopoietic Stem Cell Transplantation

Abstract: Iron overload is an adverse prognostic factor for patients undergoing hematopoietic stem cell transplantation (HSCT). In the HSCT setting, pretransplant and early posttransplant ferritin and transferrin saturation were found to be highly elevated due to high transfusion requirements. In addition to that, post-HSCT iron overload was shown to be related to infections, hepatic sinusoidal obstruction syndrome, mucositis, liver dysfunction, and acute graft-versus-host disease. Hyperferritinemia causes decreased sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 67 publications
0
34
0
1
Order By: Relevance
“…Hyperferritinemia due to multiple possible causes, such as iron overload, inflammation, or residual malignancies, has been associated with poor outcomes after allo‐HSCT . Iron overload is a major problem in allo‐HSCT recipients who receive large RBC transfusions during peri‐transplantation periods as well as during the course of chemotherapy in leukemia . This study revealed the relationship between transfusions during the course of chemotherapy in AML patients and hyperferritinemia before allo‐HSCT, suggesting its reflection of iron overload despite the limit of imperfect nature to define iron overload due to multiple function of SF.…”
Section: Discussionmentioning
confidence: 75%
“…Hyperferritinemia due to multiple possible causes, such as iron overload, inflammation, or residual malignancies, has been associated with poor outcomes after allo‐HSCT . Iron overload is a major problem in allo‐HSCT recipients who receive large RBC transfusions during peri‐transplantation periods as well as during the course of chemotherapy in leukemia . This study revealed the relationship between transfusions during the course of chemotherapy in AML patients and hyperferritinemia before allo‐HSCT, suggesting its reflection of iron overload despite the limit of imperfect nature to define iron overload due to multiple function of SF.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, ferritin appears to be a poor-prognosis marker in patients with GVHD. (25,60) The use of non-iron multivitamins is recommended in this population. (61) Nutritional recommendations in patients with Graftversus-host disease are presented in table 6.…”
Section: Magnesiummentioning
confidence: 99%
“…As summarized by Atilla et al [1], “Organ dysfunction due to iron overload may cause high mortality rates and therefore a sufficient iron chelation therapy is recommended”. We would like to share the experience from our settings where there is a very high prevalence of thalassemia and transplantation is the only curative treatment.…”
Section: To the Editormentioning
confidence: 99%